\(^2\)+6x+13=0

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

22 tháng 10 2020

\(x^2+6x+13=0\)

\(\Leftrightarrow x\left(x+6\right)+13=0\)

\(\Leftrightarrow x\left(x+6\right)=-13\)

\(\Rightarrow x=-13\)hoặc \(x+6=-13\)

th1: \(x=-13\)

\(\Leftrightarrow x=-13\)

th2: \(x+6=-13\)

\(\Leftrightarrow x=-13-6\)

\(\Leftrightarrow x=-19\)

22 tháng 10 2020

Đã âm thì không có trường hợp

18 tháng 9 2018

a,x2+6x-7=0

=>x2+7x-x-7=0

=>(x^2+7x)-(x+7)=0

=>x(x+7)-(x+7)=0 =>(x+7)(x-1)=0

=>\(\orbr{\begin{cases}x+7=0\\x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-7\\x=1\end{cases}}}\)

b, x^3-2x^2-5x+6=0

=>x(x^2-2x-5+6)=0

=>x(x^2-2x+1)=0\(^{\orbr{\begin{cases}x=0\\\left(x-1^2\right)=0\end{cases}\Rightarrow}\orbr{\begin{cases}x=0\\x=1\end{cases}}}\)

c, 2x^2-5x+3=0

=>2x^2-2x-3x+3=0

18 tháng 9 2018

\(x^3-19x-30=0\)

\(\Rightarrow x^3+5x^2+6x-5x^2-25x-30=0\)

\(\Rightarrow\left(x-5\right)\left(x^2+5x+6\right)=0\)

\(\Rightarrow\left(x-5\right)\left(x^2+2x+3x+6\right)=0\)

\(\Rightarrow\left(x-5\right)[x\left(x+2\right)+3\left(x+2\right)]=0\)

\(\Rightarrow\left(x-5\right)\left(x+3\right)\left(x+2\right)=0\)

\(\Rightarrow\hept{\begin{cases}x-5=0\\x+3=0\\x+2=0\end{cases}}\Rightarrow\hept{\begin{cases}x=5\\x=-3\\x=-2\end{cases}}\)

a: \(x^2-10x+26+y^2+2y=0\)

\(\Leftrightarrow x^2-10x+25+y^2+2y+1=0\)

\(\Leftrightarrow\left(x-5\right)^2+\left(y+1\right)^2=0\)

=>x=5 hoặc y=-1

b: \(x^2-6x+13+y^2+4y=0\)

\(\Leftrightarrow x^2-6x+9+y^2+4y+4=0\)

\(\Leftrightarrow\left(x-3\right)^2+\left(y+2\right)^2=0\)

=>x=3 và y=-2

8 tháng 5 2017

a) \(2x^2+5y^2+8x-10y+13=0\)

\(\Leftrightarrow\left(2x^2+8x+8\right)+\left(5y^2-10y+5\right)=0\)

\(\Leftrightarrow2\left(x+2\right)^2+5\left(y-1\right)^2=0\)

\(\Leftrightarrow\left\{{}\begin{matrix}2\left(x+2\right)^2=0\\5\left(y-1\right)^2=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=-2\\y=1\end{matrix}\right.\)

Vậy x=-2;y=1

b) \(3x^2+5y^2-6x+20y+23=0\)

\(\Leftrightarrow\left(3x^2-6x+3\right)+\left(5y^2+20y+20\right)=0\)

\(\Leftrightarrow3\left(x-1\right)^2+5\left(y+2\right)^2=0\)

\(\Leftrightarrow\left\{{}\begin{matrix}3\left(x-1\right)^2=0\\5\left(y+2\right)^2=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=1\\y=-2\end{matrix}\right.\)

Vậy x=1;y=-2

27 tháng 8 2017

\(a,\)\(x^4-4x^3+4x^2=0\)

\(\Leftrightarrow x^2.\left(x^2-4x+4\right)=0\)

\(\Leftrightarrow x^2.\left(x^2-2.x.2+2^2\right)=0\)

\(\Leftrightarrow x^2.\left(x-2\right)^2=0\)

\(\Leftrightarrow\orbr{\begin{cases}x^2=0\\\left(x-2\right)^2=0\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=0\\x-2=0\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=2\end{cases}}\)

\(b,\)\(x^2+5x+4=0\)

\(\Leftrightarrow x^2+x+4x+4=0\)

\(\Leftrightarrow x.\left(x+1\right)+4.\left(x+1\right)=0\)

\(\Leftrightarrow\left(x+1\right).\left(x+4\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x+1=0\\x+4=0\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=-1\\x=-4\end{cases}}\)

\(c,\)\(9x-6x^2-3=0\)

\(\Leftrightarrow-3.\left(2x^2-3x+1\right)=0\)

\(\Leftrightarrow2x^2-3x+1=0\)

\(\Leftrightarrow2x^2-2x-x+1=0\)

\(\Leftrightarrow2x.\left(x-1\right)-\left(x-1\right)\)

\(\Leftrightarrow\left(x-1\right).\left(2x-1\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x-1=0\\2x-1=0\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=1\\2x=1\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=1\\x=\frac{1}{2}\end{cases}}\)

\(d,\)\(2x^2+5x+2=0\)

\(\Leftrightarrow2x^2+4x+x+2=0\)

\(\Leftrightarrow2x.\left(x+2\right)+\left(x+2\right)=0\)

\(\Leftrightarrow\left(x+2\right).\left(2x+1\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x+2=0\\2x+1=0\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=-2\\2x=-1\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=-2\\x=-\frac{1}{2}\end{cases}}\)

10 tháng 3 2020
https://i.imgur.com/YWtqvwj.jpg
11 tháng 10 2020

a/ Sai đề à??

\(\left(2x^3-3\right)^2-\left(4x^2-9\right)=0\)

\(\Leftrightarrow4x^6-12x^3+9-4x^2+9=0\)

\(\Leftrightarrow4x^6-13x^2-4x^2+18=0\)

b/ \(\Leftrightarrow\left(x^2-3\right)\left(x^2+3\right)+2x\left(x^2-3\right)=0\)

\(\Leftrightarrow\left(x-\sqrt{3}\right)\left(x+\sqrt{3}\right)\left(x^2+3+2x\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\sqrt{3}\\x=-\sqrt{3}\end{matrix}\right.\) (do \(x^2+3+2x>0\forall x\))

d/ \(\Leftrightarrow2\left(x+5\right)-x\left(x+5\right)=0\)

\(\Leftrightarrow\left(2-x\right)\left(x+5\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-5\end{matrix}\right.\)